Aktualisasi Revolusi Mental dalam Pengelolaan Dana Desa (Analisis Tafsir Ekonomi Q.S.Yusuf [12]: 55) - Muhammad Amin; Azima Azima (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
Dana Desa are one of the most effective policies in village development with the completion of various kinds of infrastructure in the village. On the other hand, this policy caused side effects in the form of criminal acts of corruption against these funds. Through the interpretation of Q.S. Yusuf verse 55, the author offers the actualization of the spirit of mental revolution in the management of village funds through measures to strengthen integrity, increase professionalism, innovation, responsibility, and broaden horizons. Through these steps, the village fund policy can be implemented completely and right on target.